Incidence of Penile Fracture in Iran, a Cross-Sectional Study - Rahavian, Amir Hossein; Hosseini, Mohammad Ali; Hosseini, Jalil (Archives of Men’s Health, 2021)
Background: Penile fracture is a urological emergency requiring proper diagnosis and treatment. Limited studies conducted in Iran have reported high prevalence of this problem (9.9 per 100,000 male population). In this study, we also examined the causes and symptoms, as well as the type of treatment physicians choose so that in the future, we can use this data to educate physicians and other people in the community about this disease. Methods: First, all urologists across the country were contacted and informed about the project. Then, from February 2017 to February 2018, a pre-prepared questionnaire containing the required information was sent to them and they were asked to complete and send this questionnaire in case of a penile fracture. Then, every two weeks, we reconnected all urologists in different ways (email, phone call, virtual networks, etc.) and collected relevant data. Finally, all data were analyzed using SPSS software, version 19. Results: The incidence of penile fractures was estimated to be 2.5 per 100,000 men (from 0.38 in the age range of 69-60 years to 3.9 in the age range of 39-30 years). The most common causes of penile fractures were sexual intercourse (64.8%), followed by non-sexual trauma (16.9%) and masturbation (13.3%). Pain, edema and discoloration of the penis were the most common symptoms at the time of admission (83.6%) and most patients (84%) had referred to a physician within the first 24 hours after the accident. 78.9% of urologists believed in emergency surgical treatment, while 20.3% believed in delayed surgical treatment and 0.7% believed in supportive treatment. Conclusion: Because of the cultural diversity of Iran, the rate of penile fracture is very different in different parts of Iran, but its rate is much lower than previous studies.